STRATEGI PENGEMBANGAN AGRO PUNCAK BUKIT CATU BERBASIS AGROWISATA BERKELANJUTAN - I Gusti Ketut Adi Winata; I Made Dwita Atmaja; Ni Made Wulan Sari Sanjaya (Jurnal Ekonomi dan Bisnis (EK dan BI), 2023)
The diversity of tourist attractions in Bali causes competition between tourist attractions to become increasingly fierce, especially in the Tabanan Regency area. Therefore, it is necessary to formulate a strategy for developing Puncak Bukit Catu Agro based on sustainable agrotourism. The objectives of this research include: (1) determining a development strategy for Puncak Bukit Catu Agro based on sustainable agrotourism; (3) determine the priority strategy for the development of Puncak Bukit Catu Agro based on Sustainable Agrotourism. The main method used in this research is the descriptive analysis method. The data collection techniques used in this research are the Interview and Questionnaire Method. The analysis used in this qualitative research is data analysis using an interactive model. Apart from that, SWOT and QSPM matrix analysis is also used in formulating the strategy to be implemented. Agro Puncak Bukit Catu is an agrotourism that has an impact on the development of rural tourism in the village of Bukit Catu. Agrotourism is an economic activity that has potential social, economic and environmental impacts. The qspm matrix shows that the position of Puncak Bukit Catu Agrotourism is in quadrant I. This focuses on product development strategies. This means that Puncak Bukit Catu Agrotourism needs to develop products.